PENGARUH MANAJEMEN LABA RIIL TERHADAP KINERJA PERUSAHAAN SETELAH KONVERGENSI INTERNATIONAL FINANCIAL REPORTING STANDARDS (IFRS) - Megawati Marine Putri; Akhmad Saebani; Andi Manggala Putra (Universitas Pakuan, 2020)
This study aims to examine the effect of real earnings management on company performance after IFRS convergence. Research sampling is 329 selected by the purposive sampling method. The results showed that after the convergence of IFRS, real earnings management still occurred in the company as a substantive method from other methods of performance improvement. Unreasonably increased sales and excess production levels do not affect the company's performance. While the decrease in discretional expenses has a positive effect on company performance. companies can use real earnings management as another way to improve company performance that is measured in broad terms through the value of company assets and the amount of profit generated by the company in a certain period. Although it does not provide a large enough influence in improving company performance. Therefore it needs to be further analyzed for company managers to add other ways to improve company performance.